ANALISIS PENGARUH PENAGIHAN PAJAK DENGAN SURAT PAKSA TERHADAP PENERIMAAN PAJAK DI KANTOR PELAYANAN PAJAK PRATAMA ARGAMAKMUR PROVINSI BENGKULU - Yuspitara, Adhitya; Susena, Karona Cahya; Herlin, - (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2017)
Adhitya Yuspitara, Karona Cahya Susena, Herlin; The purpose of this study is to provide an overview of tax collection actions with a forced letter made in the tax office Pratama Argamakmur, Knowing the effect of tax collection by a forced letter in the tax service office pramama argamakmur in order to increase tax revenue in KPP Prtama Argamakmur in particular corporate income tax. Data collection method used is secondary data in the form of documentation. The method of analysis used is simple linear regression analysis and hypothesis testing with t test. Based on the results of research and data analysis on the effect of tax collection with a letter of force against tax revenue in the tax office Pratama Argamakmur can draw the conclusion of the results of simple correlation analysis, simple linear regression value Y=7.105.100,391+977.683,917X r value = 0,803 The coefficient of determination = 0.645 and the value of t arithmetic greater than t table is 5,714>1.725 it indicates that Ho is rejected and Ha received which means that there is influence of tax collection with the letter of force against the tax revenue.Key Words: Tax collection and Tax Receipts